Benefits of complementary therapy with insulin aspart versus human regular insulin in persons with type 2 diabetes mellitus - Chlup, Rudolf; Zapletalová, Jana; Sečkař, Pavel; Malá, Eva; Doubravová, Blanka; Táncosová, Svatava; Chlupová, Ludmila; Pukowietz, Libor; Zatloukal, Petr (Diabetes technology & therapeutics, 2007)
BACKGROUND: Absorption rates of the phosphate-buffered insulin analogs aspart, lispro, and glulisine prevail over that of regular human insulin. The aim of this prospective observational open-label controlled study was to compare the effects of aspart and human regular insulin resulting from their sequential long-lasting routine administration in small preprandial boluses to individuals with type 2 diabetes according to identical algorithms. METHODS: Fifty-seven individuals with type 2 diabetes 64.0 +/- 1.29 (mean +/- SE) years old with diabetes' duration of 12.4 +/- 1.06 years, treated with human regular insulin for 5.2 +/- 0.44 years, and a serum C-peptide level of 1.1 +/- 0.10 nmol/L were enrolled into the study. Following two checkups performed in the course of the 364 +/- 17.9-day baseline period, human regular insulin was replaced with aspart in equivalent boluses, and two checkups in the course of 330 +/- 11.1-day sequential period were performed. The control group consisted of 17 individuals with type 2 diabetes 68.4 +/- 2.36 years old with diabetes' duration of 9.9 +/- 1.57 years, treated with insulin for 4.2 +/- 0.57 years, and a C-peptide level of 1.1 +/- 0.11 nmol/L. Data were analyzed using the statistical program SPSS version 10.1. (SPSS, Inc., Chicago, IL). RESULTS: Following the switch from human regular insulin to aspart, hemoglobin A1c (HbA1c) decreased from 8.4 +/- 0.23% at baseline to 7.9 +/- 0.17% (P = 0.031), and thereafter to 7.5 +/- 0.20% (P < 0.001), while plasma glucose concentrations in 10-point profiles, daily insulin dose (37.1 +/- 1.39 IU/day), body mass index (BMI) (30.5 +/- 0.82 kg/m(2)), and frequency of hypo- and hyperglycemic episodes did not change (P > 0.05). Patients quote satisfaction was good. No adverse events were recorded. In the control group, no significant change of baseline HbA1c (8.4 +/- 0.54%), insulin dose (33.1 +/- 3.17 IU/day), and BMI (32.1 +/- 1.12 kg/m(2)) was found. CONCLUSION: Aspart appears to be more effective than human regular insulin for complementary insulin treatment in individuals with type 2 diabetes.
Keywords: spokojenost pacientů; financování organizované; C-Peptide; Female; Patient Satisfaction; výsledek terapie; ženské pohlaví; lipidy; Diabetes Mellitus, Type 2; lidé; Blood Glucose; Hypoglycemic Agents; diabetes mellitus 2. typu; Insulin; Lipids; Treatment Outcome; Financing, Organized; hypoglykemika; prospektivní studie; Male; Aged; Prospective Studies; index tělesné hmotnosti; glykovaný hemoglobin; lidé středního věku; senioři; mužské pohlaví; C-peptid; Body Mass Index; inzulin; krevní glukóza; Glycated Hemoglobin; Middle Aged; Humans